Unraveling the Drivers of Lecturer Performance: A Systematic Review of Reward Systems, Visionary Leadership, Organizational Culture, and Commitment - Kabul Praptiyono; Sri Setyaningsih; Rita Retnowati (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2026)
This study aims to systematically examine and synthesize the factors that influence lecturer performance in higher education, particularly those related to the reward system, visionary leadership, organizational culture, and organizational commitment. The study used a Systematic Literature Review (SLR) approach with the PRISMA model, through the process of identifying, filtering, selecting, and including articles from reputable databases, resulting in 57 relevant articles for analysis. The results showed that the reward system was the most consistent factor directly influencing lecturer performance, followed by organizational culture, which plays a role in creating a conducive work environment and encouraging innovation. Meanwhile, visionary leadership showed an inconsistent direct influence, but contributed indirectly through mediating variables. In this case, organizational commitment emerged as a key variable (key mediator) that bridges the influence of various organizational factors on lecturer performance. The discussion shows that lecturer performance is influenced by complex interactions between structural and psychological factors that are multidimensional and non-linear. The implications of this research emphasize the importance of an integrative approach in managing lecturer performance through strengthening the reward system, developing an adaptive organizational culture, implementing effective leadership, and increasing organizational commitment as a strategy for improving sustainable performance.